2010
DOI: 10.1111/j.1439-0396.2010.01056.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of replacing corn with glycerol on ruminal bacteria in continuous culture fermenters

Abstract: The effects of substituting corn with glycerol on DNA concentration of selected ruminal bacteria were investigated using continuous fermenters. Four continuous culture fermenters were used in a 4 × 4 Latin Square design with four 10 days consecutive periods. Treatment diets (60:40 forage to concentrate) were fed at 45 g/day dry matter (DM) in three equal portions. Glycerol (0.995 g/g glycerol) was used to replace corn in a grain mix at proportions of 0% (T0; control), 15% (T15), 30% (T30) and 45% (T45). On day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 26 publications
(39 reference statements)
2
44
0
Order By: Relevance
“…lactilytica (HOBSON and MANN, 1961). ABU et al, (2011) showed that glycerol substitution had no effects on pH, ammonia nitrogen concentration, and dry matter digestibility in vitro fermentations using cow rumen fluid as an inoculum. The numbers of Butyrivibrio fibrisolvens, Clostridium proteoclasticum, and S. ruminantium decreased under high level glycerol concentration diet but no differences for Ruminococcus albus and Succinivibrio dextrinosolvens among diets with different glycerol concentrations were observed.…”
Section: Resultsmentioning
confidence: 99%
“…lactilytica (HOBSON and MANN, 1961). ABU et al, (2011) showed that glycerol substitution had no effects on pH, ammonia nitrogen concentration, and dry matter digestibility in vitro fermentations using cow rumen fluid as an inoculum. The numbers of Butyrivibrio fibrisolvens, Clostridium proteoclasticum, and S. ruminantium decreased under high level glycerol concentration diet but no differences for Ruminococcus albus and Succinivibrio dextrinosolvens among diets with different glycerol concentrations were observed.…”
Section: Resultsmentioning
confidence: 99%
“…However, while glycerin can increase the digestibility of diets because of its higher digestibility, its inclusion causes a reduction of the digestibility of the fiber fraction of diets because of the negative impact on the population of rumen fibrolytic bacteria (Abo El-Nor et al, 2010;Abughazaleh et al, 2011). In this study, it is believed that the positive and negative aspects of crude glycerin on the apparent digestibility of diets were offset, resulting in no effect of crude glycerin levels on the digestibility coefficients of dry matter, crude protein, ether extract, and total digestible nutrients of the diets.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research involving glycerol has focused on using glycerol as a replacement for barley (Avila et al 2011;Harzia et al 2013) and/or corn (Donkin et al 2009;AbuGhazaleh et al 2011) in ruminant diets to reduce costs. However, there is evidence that glycerol is a glucogenic source (Johnson 1954;Re´mond et al 1993 (1 ) (National Research Council 2001;DeFrain et al 2004).…”
Section: Glycerolmentioning
confidence: 99%
“…Although positive effects of glycerol (70, 140, or 210 g kg (1 DM) on NDF digestibility have been reported (Avila et al 2011;Meale et al 2013), some in vitro studies (Roger et al 1992;Abo El-Nor et al 2010) show an inhibitory cellulolytic effect of glycerol when added at 5, 7.2, or 10.8% of DM. Nevertheless, the mechanisms by which glycerol inhibits cellulolytic bacteria are still not clear (AbuGhazaleh et al 2011;Edwards et al 2012), although it is evident that glycerol affects adhesion and growth of rumen microorganisms (Roger et al 1992).…”
Section: Glycerolmentioning
confidence: 99%
See 1 more Smart Citation